"JUSTICE ASPECTS IN THE OUTSOURCING WORK AGREEMENT IN THE MIDDLE OF THE COVID-19 PANDEMIC" - Agustina Balik; Novyta Uktolseja (SASI, 2021)
Many businessmen stated that it was difficult to survive during the Covid-19 pandemic situation which resulted in them having made layoffs, even providing unpaid leave or being sent home. This was done solely so that the company could survive the Covid-19 pandemic. Related to the Covid-19 pandemic problem which resulted in workers being laid off and sent home, it is deemed that it does not fulfill a sense of justice for the workforce. This is because the layoffs given to workers are felt to be very sudden, especially since workers do not make mistakes that could harm the company. Therefore, the aim of this research is to study and analyze aspects of fairness in outsourcing work agreements in the midst of the Covid-19 pandemic. The method used in this study is a normative juridical method using primary and secondary legal materials through a statute approach and a conceptual approach. The existing legal materials are then analyzed qualitatively in order to answer the existing problems. The results show that if the principles of justice put forward by the principles governing the state of workers who are laid off and sent home during the Covid-19 pandemic, then they should be treated fairly, so as to fulfill a sense of justice for the workforce. The respect given by the company to the workforce by giving what is rightfully the workforce can proportionally make the workforce accept the company's decisions gracefully, even though this is not in accordance with the work agreement that has been previously agreed. This can be applied and implemented that the Covid-19 pandemic is an overmacht, which cannot be avoided by anyone.